Culture Influence in Political Communication - Musliamin Musliamin (Palakka : Media and Islamic Communication, 2021)
This study discusses "The Influence of Culture in Political Communication".The aim of this research is to understand the influence of the concept of culture on political communication and to strengthen our understanding of the causality involved in creating effective communication in creating a positive political culture. This research or library research, this research explores and understands the influence of Political Communication Culture. Library research is a series of activities related to methods of collecting library data, reading, and recording and managing library collection materials. The results showed that the influence of political communication culturetends to shift. Currently, by prioritizing democratization, the culture of political communication tends to be open, transparent, rational and can be conveyed through open ways. Keywords: Culture Influence; Political Communication.